Strategi Inovasi dan Kolaborasi Bank Wakaf Mikro Syariah dan Umkm Indonesia di Era Digital - Nugroho Heri Pramono; Asri Nur Wahyuni (Jurnal Ilmiah Ekonomi Islam, 2021)
The industrial revolution 4.0 should make financial information for stakeholders more accountable. Therefore, this study contributes to providing a business paper with the aim of identifying and explaining the innovation and collaboration strategies of Islamic micro waqf banks and Indonesian micro, small and medium enterprises in the digital era. The research method used is descriptive statistical analysis, internal and external strategic analysis and SWOT analysis. The population of this study consisted of 11 Islamic micro waqf banks (BWMS) located in Central Java, 5 experts in Islamic finance, and fintech. The results showed that BWMS and sharia fintech were in a growing condition. In addition, BWMS and sharia fintech are also in the quadrant of the conglomeration diversification strategy. This strategy seeks to create new products to gain a wider market. Therefore, to make new products more innovative and a wider market, strategic innovation was made by creating sharia fintech that collaborated with BWMS and micro, small and medium enterprises.